Consumer health risk assessment of Arsenic and Mercury in hen eggs through Monte Carlo simulations - Abdol-samad Abedi; Hedayat Hoseini; Fatemeh Mohammadi-Nasrabadi; Negar Rostami; Fatemeh Esfarjani (BMC, 2023)
Abstract Background This study was conducted to assess the concentration of heavy metals (arsenic and mercury) and estimate the probability that consumption of hen egg products collected in Iran has carcinogenic or non-carcinogenic consequences. Methods A total of eighty-four hen eggs from 21 major brands were randomly selected from among thirty local supermarkets in two seasons (winter (January) and summer (August) 2022). Arsenic (As) and Mercury (Hg) was determined by using ICP-MS. The human health risk assessment refers to the formulation of the USEPA standard focused on Estimated Daily Intake (EDI), International Lifetime Cancer Risk (ILCR), Target Hazard Quotient (THQ), and Monte Carlo simulation (MCS) as a probabilistic method. Data analysis was carried out using the statistical software SPSS. Differences in mean concentrations of As and Hg in two seasons were tested by paired t-test. Results Over two seasons, the average As and Hg concentrations in hen eggs were 0.79 and 0.18 µg.kg−1, respectively. Seasonal difference in As concentration (p = 0.451) was not significant, whereas that of Hg concentration (p < 0.001) was significant. The calculated value of EDI was 0.29 µg As/day and 0.06 µg Hg/day. The EWI in the maximum scenario of as level in hen eggs was estimated to be 8.71 µg As and 1.89 µg Hg/month for Iranian adults. THQ's mean for As and Hg in adults was determined to be 0.00385 and 0.00066, respectively. In addition, ILCRs by MCS for As were 4.35E-4. Conclusion In total, the result indicates that there was not a significant risk of developing cancer; the calculation of THQ was still below the accepted level of 1, indicating that there was no risk while, according to most regulatory programs (ILCR > 10− 4) shows a threshold carcinogenic risk of arsenic through consuming in hen eggs. Therefore, policymakers need to be aware that it is prohibited to establish chicken farms in heavily polluted urban areas. It is essential to regularly conduct examinations to measure the presence of heavy metals in both ground waters used for agriculture and the feed provided to chickens. Additionally, it is advisable to focus on raising public awareness about the importance of maintaining a healthy diet.